Neighbourhood deprivation and incidence of coronary heart disease: a multilevel study of 2.6 million women and men in Sweden. Issue 1 (18th December 2003) - Sundquist, K; Malmström, M; Johansson, S-E
Abstract : Study objective: To examine whether neighbourhood deprivation predicts incidence rates of coronary heart disease, beyond age and individual income. Design: Follow up study from 31 December 1995 to 31 December 1999. Women and men were analysed separately with respect to incidence rates of coronary heart disease. Multilevel logistic regression was used in the analysis with individual level characteristics (age, individual income) at the first level and level of neighbourhood deprivation at the second level. Neighbourhood deprivation was measured at small area market statistics level by the use of Care Need Index. Setting: Sweden. Participants: All women and men aged 40–64 in the Swedish population, in total 2.6 million people. Main results: There was a strong relation between level of neighbourhood deprivation and incidence rates of coronary heart disease for both women and men. In the full model, which took account of individual income, the risk of developing coronary heart disease was 87% higher for women and 42% higher for men in the most deprived neighbourhoods than in the most affluent neighbourhoods. For both women and men the variance at neighbourhood level was over twice the standard error, indicating significant differences in coronary heart disease risk between neighbourhoods. Conclusions: High levels of neighbourhood deprivation independently predict coronary heart disease for both women and men. Both individual and neighbourhood level approaches are important in health care policies.